2022
DOI: 10.12998/wjcc.v10.i23.8161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographic features and laboratory parameters between COVID-19 deceased patients and surviving severe and critically ill cases

Abstract: BACKGROUND Coronavirus disease 2019 (COVID-19) has been far more devastating than expected, showing no signs of slowing down at present. Heilongjiang Province is the most northeastern province of China, and has cold weather for nearly half a year and an annual temperature difference of more than 60ºC, which increases the underlying morbidity associated with pulmonary diseases, and thus leads to lung dysfunction. The demographic features and laboratory parameters of COVID-19 deceased patients in He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Infection with the Delta variant is also considered to induce an increase in D-dimer serum levels [ 22 ]. Other studies and meta-analyses have also found that D-dimer levels were noticeably greater in COVID-19 patients than in healthy controls, and this coagulation derangement has been correlated with disease severity and higher mortality, confirming our findings [ 6 , 18 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, contrary to our findings, a study by Shulman AH et al, 2022 carried out in Johannesburg showed that D-dimer serum levels in patients infected by the Omicron variant did not rise as much compared to those infected by the Delta variant [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Infection with the Delta variant is also considered to induce an increase in D-dimer serum levels [ 22 ]. Other studies and meta-analyses have also found that D-dimer levels were noticeably greater in COVID-19 patients than in healthy controls, and this coagulation derangement has been correlated with disease severity and higher mortality, confirming our findings [ 6 , 18 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, contrary to our findings, a study by Shulman AH et al, 2022 carried out in Johannesburg showed that D-dimer serum levels in patients infected by the Omicron variant did not rise as much compared to those infected by the Delta variant [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…In everyday clinical practice, specific laboratory parameters are used to evaluate the overall clinical status of patients presenting at the emergency departments of hospitals and, later on, to monitor their ongoing condition in case of hospitalization. Variations of such parameters have been deemed to predict the severity of the infection and have been correlated with clinical outcomes [ 6 ]. However, to the best of our knowledge, there is no data illustrating how specific laboratory parameters may vary among patients affected by different SARS-CoV-2 VOCs documented by full genome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The Wang et al [ 1 ] study demonstrated a strong significant correlation between CRP in the sera of geriatric patients ( r = 0.67; P = 0.023) and the fatality rates among cases, which was consistent with previous studies[ 3 , 10 ].…”
Section: To the Editorsupporting
confidence: 82%
“…With interest, we read Wang et al 's study published in World J Clin Cases 2022, which discussed differences in lab biomarkers and patient risk factors linked to fatal outcomes in elderly patients following the acquisition of coronavirus disease 2019 (COVID-19)[ 1 ]. Advanced life expectancy and improved medical services have increased the number of geriatrics in the community, who represent a critical vulnerable group for COVID-19[ 2 ].…”
Section: To the Editormentioning
confidence: 99%
“… 4 6 In the absence of available targeted therapy, timely detection of patients at high risk of disease deterioration and effective tailored interventions at an early stage are important and essential clinical management strategies for COVID-19 patients, in addition to active preventive measures. 7 , 8 Therefore, every effort should be made to explore simple and effective indicators in clinical practice so as to achieve the above goals and thus improve the prognosis of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%